DIETARY ROSEMARY SUPPLEMENTATION AND ITS INFLUENCE ON SOME SEMEN AND BLOOD BIOCHEMICAL TRAITS OF HOLSTEIN BULLS - M.S. Abdulhameed,; S. M. Eidan, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study investigated supplementing dried rosemary leaves to the diet of some semen, as well as blood biochemical traits in Holstein bulls. The eight bulls were divided equally into two groups (4bull/group). Bulls' in the first group were fed a diet without additives (control group). The bulls in the second group were fed a diet supplemented with 250mg rosemary per bull daily for 12 weeks, preceded by a two-week preliminary period. We detected some of the rosemary's active components. The semen was collected and evaluated weekly for 12 weeks. The serum concentrations of glucose, urea, aspartate, and alanine transaminase were determined. The active components analysis of rosemary revealed it contains phenolics (Gallic acid), flavonoids (Luteolin, Quercetin, Rutin, Kaempferol, Tannic acid, and Epicatechine), saponins, and vitamins (A, E, and C). The results revealed higher (P≤0.05) mass activity, motility, live sperm, and normal morphology of sperms in the rosemary group than in the control group. The rosemary group recorded a lower (P≤0.05) semen volume, head sperm and total abnormalities, glucose, and urea than the control group. In conclusion, the active components, especially flavonoids and phenolics in rosemary, may improve insulin sensitivity by testis to take glucose, which somewhat ameliorates the semen quality of Holstein bulls and overcomes some climate change influences on sustainable consumption and production.